PENYELESAIAN KREDIT MACET SEKTOR AGRIBISNIS PADA PERUSAHAAN DAERAH BPR ROKAN HULU MENURUT UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 7 TAHUN 1992 TENTANG PERBANKAN - Nadia Hayatun Nufus; Hayatul Izmi; Ulfia Hasanah (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2022)
One of the financial institutions experiencing credit problems in the Pasir Pangaraian area is PD BPR Rohul. The number of customers in 2021 is 1170 customers with a loan amount of Rp. 37,091,711,617, where bad loans amounted to Rp. 2,388,181,879 of which agribusiness credit is the type of credit with the most bad loans, which is Rp. 1,600,782,615. The problems in this study are the factors that cause the occurrence of bad loans in the Agribusiness Sector at the Rokan Hulu Rural Bank Regional Company, how to resolve the Agribusiness Sector bad loans and the obstacles faced by the Rokan Hulu Rural Bank Regional Company in credit settlement. Agribusiness sector traffic jam. This research is a sociological research located at the Regional Company of BPR Rokan Hulu. The data sources used in this research are Primary Data, Secondary Data and Tertiary Data with Data Collection Techniques using Interviews and Library Studies. Based on the discussion, the authors conclude that the rights and obligations of each party based on the credit agreement include the ceiling and intended use of credit, term and schedule, interest rates, fees and administrative costs, insurance, power of attorney, guarantees, fines, interest in arrears, defaults, execution of collateral, change of domicile, notification, change, validity period, legal domicile and closing articles. Settlement of bad loans in the Agribusiness Sector at the Rokan Hulu Rural Bank Regional Company is carried out by rescheduling, reconditioning and liquidation. Obstacles faced by the Rokan Hulu People's Bank Regional Company in resolving bad loans in the Agribusiness Sector in the form of agribusiness businesses that are not managed properly, collateral sold privately, customers experience ongoing internal problems, customers are in debt, customers are difficult to communicate with, change addresses, influence PD BPR Rohul staff and customers avoid deliberations.